2014
DOI: 10.1002/eji.201444588
|View full text |Cite
|
Sign up to set email alerts
|

pDCs efficiently process synthetic long peptides to induce functional virus‐ and tumour‐specific T‐cell responses

Abstract: Keywords: Cancer r Cross-presentation r Long peptides r Plasmacytoid dendritic cells r Viral infectionAdditional supporting information may be found in the online version of this article at the publisher's web-site IntroductionDeveloping efficient therapeutic strategies for cancer and viral infection remains challenging. Successful immunotherapies should elicit robust cell-mediated immunity that is able to eliminate tumour-or virus-infected cells, since strong and multi-specific cytotoxic T lymphocytes (CTLs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…Recent studies in mice have shown that pDCs can effectively induce anti-tumor CD8+ T-cell responses [ 30 ], and that pDCs efficiently cross-present TAA to trigger T-cell responses [ 28 ]. In the present study, we asked if there was any correlation between survival, patients’ in vitro T-cell responses to Her-2 peptides, and frequencies of circulating DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in mice have shown that pDCs can effectively induce anti-tumor CD8+ T-cell responses [ 30 ], and that pDCs efficiently cross-present TAA to trigger T-cell responses [ 28 ]. In the present study, we asked if there was any correlation between survival, patients’ in vitro T-cell responses to Her-2 peptides, and frequencies of circulating DCs.…”
Section: Discussionmentioning
confidence: 99%
“…An effective way to induce both TAA-reactive CD4+ and CD8+ T-cell responses is by using synthetic long peptides (SLPs) [ 25 , 26 ]. Antigen presentation by pDCs could contribute to the induction of specific CD4+ and CD8+ T-cell responses [ 27 , 28 ], but this would be contrary to the findings discussed above implying that high levels of pDCs in the tumor and low levels in the blood have a negative prognostic impact. Thus, the present study focuses on investigating the prognostic relevance of circulating antigen-presenting cells including total DCs, mDCs and pDCs separately, together with functional Her-2-reactive T-cells assayed in vitro, and an assessment of the impact of immunosuppressive cells on 5-year survival of breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“… 42 Most cross-presentation studies have been carried out using full-length proteins as the source of peptides but a few recent studies report that SLP can be cross-presented in mice by different types of DCs from BMDCs to pDCs. 10,12 It is possible that the uptake and processing of antigenic peptide substrates by the pAPCs for cross-presentation is specialized toward a certain type, and context, of peptide material and it will be interesting to compare if cross-presentation by different types of pAPCs depends on the nature of the antigen. In view of this, it is interesting that we detect PTP products in the exosomes of tumor-derived cell lines and that PTP-loaded exosomes alone are sufficient to trigger an efficient cross-presentation by BMDCs.…”
Section: Resultsmentioning
confidence: 99%
“… 8,9 Synthetic long peptides (SLP) of 22 to 24 amino acids of the Ovalbumin or HIV-1 Gag proteins are a better source of peptides for the cross-presentation pathway as compared to full-length proteins. 10-12 Together with the fact that antigenic peptides derived from non-canonical mRNA translation such as intron or alternative open reading frames have been detected on MHC class I molecules highlights the need to investigate the role of alternative sources of peptides for CD8 + T cell activation against tumor cells. 13-15 Recent studies have shown that alternative translation products such as DRiPs (defective ribosomal products) 16 or pioneer translation products (PTPs) constitute an important source of peptides for the endogenous class I pathway.…”
mentioning
confidence: 99%
“…Blood and lymphoid organ pDCs cross-present efficiently soluble ( 41 , 44 , 67 , 70 , 71 ), viral ( 71 74 ), cell-associated antigen ( 67 , 75 ), or antigen targeted to surface receptors such as CD40, DCIR, CD205, BDCA2/CD303, or CD32 ( 67 , 69 , 76 ).…”
Section: Is There a Functional Specialization Of Human DC Subsets?mentioning
confidence: 99%